The effect of different poly fibers separator-modified materials on blocking polysulfides for high performance Li-S batteries - Meng, Ling; Sun, Zhaoxia; Sun, Guanghang; Zhang, Xiting; Dan, Meng; Long, Jin; Hu, Jian (Frontiers in Chemistry, 2022)
Herein, we reported that KOH impregnation can promote a large number of nitrogen self-doped micropores generation with fruitful O/N containing groups during the carbonized process of poly (p-phenylene terephthalamide) and poly (p-phenylene benzobisoxazole) fibers (denoted as PPTA and PBO, respectively) by one-step preparation. The intrinsical insulation, volume change and shuttle effect of polysulfides then can be significantly improved by both physical confinement and chemical anchoring of polysulfides especially for the PBO coated separator. The primary discharge capacity of cell with PBO coated separator achieves 1322 mAh g-1, which retains 827 mAh g-1 even after 200 cycles at 0.2 C. The specific reversible discharge capacity maintains 841 mAh g-1 at 5 C, with 99.7% coulomb efficiency. The nitrogen self-doped carbon sheet etched by KOH with the simple one-step preparation, which has promising application toward Li-S batteries.